The stability of the world image in creating a global sense of security. - Stanisław Ciupka (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2020)
The concept of safety has changed over the centuries and has been taken into account by many different factors. This was because some stability only covered some areas of human life and others were subject to change. Often the changes were created by different temporary fashions and trends. By referring to different philosophical concepts over the centuries, we would like to point out that many researchers claim that there is a constant trend to question a stable, certain world picture in global dimensions. If this thesis is true, then it begins to live and function, both in the individual and social dimension in an increasingly dangerous global world.